Teenagers’ wellness in divorced families: A phenomenological study / Sarada Devi R.Subramaniam - Sarada Devi , R.Subramaniam (2020)

(untitled)
This study aimed to explore an in-depth understanding on the wellness of teenagers in divorced families. This qualitative study used the phenomenological approach to explore the experience of ten teenagers living with single mothers after the divorce of their parents. Participants in this research are 10 teenagers age between 16 to 18 years’ old who lived with their mothers after their parents' divorce. The duration of their parents' divorce during the data collection was in the range of one to ten years.Data were collected using semi-structured interviews and document analysis by social media. Data were analysed using NVIVO12 software. Nine themes and 26 sub-themes emerged from this study. Three main themes and ten subthemes answered the first research question on, what is the meaning of wellness among teenagers in divorced families? Another three more theme and eight sub themes answered the second research question on, what are the perception of teenagers towards wellness in divorced families? The remaining three themes and eight sub themes answered the third research question on, how does divorce changes the wellness in teenager’s life? In conclusion, teenagers’ in this study accepted the changes that occurred as a result of parental divorce. The implications of this study is viewed from three aspects; 1) practical implications for professions such as counselors, 2) theoretical implications for future research, and 3) implications in the field of education for the wellness of the community. The information extracted from the findings of this study can help counselors to understand better on the actual living experience of teenagers in divorced families. The study also helps counsellors to understand how some teenagers manage to live a successful life and fulfilling all the wellness of life in spite of living in divorced families. As this study only focus on teenagers living with their mother after their parents’ divorce, it recommends future researchers to consider exploring areas of wellness among teenagers in joint custody parents or teenagers living with their single father after the parental divorce.